Nelson-Siegel yield curve model estimation and the yield curve trading in the Croation financial market - Davor Zoricic; Marko Badurina (UTMS Journal of Economics, 2013)
The paper examines the possibility of yield curve estimation in the illiquid Croatian financial market using the parametric Nelson-Siegel model. Furthermore bond trading strategies are being discussed regarding the estimated model parameters. Research findings suggest a minimum of 5 data points per observation in order to obtain Nelson-Siegel parameters. The evolution of the parameters seems to be in line with macroeconomic theory considering the state of Croatian economy in the analyzed period. This is especially true in the case of pure kuna instruments sample while some peculiarities have been detected in the sample referring to the euro denominated instruments. However further research should be conducted regarding the applicability of the model for the yield curve trading purposes due to market's illiquidity.
Keywords: G12; 330; yield curve model; bond trading strategies